UPGRADING COAL LOW QUALITY WITH DRYING PROCESS WITHOUT OXYGEN - Joni Pradinata; Rijal Abdullah; Ansosry Ansosry (Departemen Teknik Pertambangan FT UNP, 2018)
kcal/kg that accumulate in stockpile PT. Nusa Alam Lestari. The authorconducted a preliminary survey to determine the amount of low quality coal inPT. Nusa Alam Lestari. In February 2017 the number of coal with a calorie valuebelow 5100 kcal /kg - 5500 kcal / kg on the stockpile of seam stack at 10422 tonsof stockpile.Here are several kinds of coal upgrading process, one of them is dryingprocess. Coal Drying aims to remove or decrease the water content contained incoal, so that with reduced moisture content is able to increase the calorific valueof coal.In the process of upgrading with the drying process (Coal Drying)obtained coal calorific value by using Furnance Carbolite to influencetemperature and reaction time that is at 400⁰C for 1 hour produce coal withcalories 5,697,94 kkal / kg. At 400⁰C for 2 hours produces coal with a calorificvalue of 5,987.8 kcal kg. At 400⁰C for 3 hours produces coal with a calorificvalue of 6,182.70 kcal/kg. At 500⁰C for 1 hour produce coal with a calorific valueof 6,192.44 kcal/kg. At a temperature of 500⁰C for 2 hours yields a coal calorificvalue of 6,233.86 kcal / kg. At a temperature of 500⁰ for 3 hours yields a calorificvalue of 6,219.24 kcal / kg. At 600⁰C for 1 hour yields a calorific value of6,423.15 kcal/ kg. At 600⁰C for 2 hours 6,470.15 kcal/kg. At 600⁰C for 3 hoursyields a caloric value of 6,375.14 kcal/kg.In this research, the optimum caloric value obtained at drying process is600⁰C for 2 hours with decreasing water content 3,95%. In the drying process tothe effect of temperature and calorie reaction time rose from 5,457.99 kcal/kg to6,470.15 kcal/kg.